2021
DOI: 10.2147/cmar.s305719
|View full text |Cite
|
Sign up to set email alerts
|

High SQLE Expression and Gene Amplification Correlates with Poor Prognosis in Head and Neck Squamous Cell Carcinoma

Abstract: Objective Squalene epoxidase (SQLE) is considered a metabolic oncogene, but its biological function and prognostic value in head and neck squamous cell carcinoma (HNSCC) remain unclear. We aimed to evaluate the role of SQLE in the occurrence and development of HNSCC through bioinformatics analysis, and validation experiments. Methods Transcriptomic, genomic, and clinical data from The Cancer Genome Atlas were used for pan-cancer analysis. SQLE expression in HNSCC was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…It has been reported that SQLE participated in the regulation of tumor development and progression. Liu et al preliminarily reported SQLE upregulation in HNSCC cells might predict poor prognosis [7]. To our knowledge, it is the first study to illustrate the functional mechanisms of SQLE in HNSCC.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that SQLE participated in the regulation of tumor development and progression. Liu et al preliminarily reported SQLE upregulation in HNSCC cells might predict poor prognosis [7]. To our knowledge, it is the first study to illustrate the functional mechanisms of SQLE in HNSCC.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, KEGG analysis showed SQLE was closely related with cell-cell interaction. Also, Liu et al illustrated SQLE expression was negatively associated with the infiltration of CD8+ T cells, follicular helper T cells, and regulatory T cell infiltration and mast cell activation in HNSCC, indicating SQLE function important role in regulating tumor microenvironment (TME) and more experimental evidence might be given [7]. Therefore, SQLE may promote the progression of HNSCC through various mechanisms, which needs to be furtherly determined in future work.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite this, a specific examination of trunSM levels had not been performed in any cancer type prior to our study. We found that total SM levels were reduced in endometrial tumor tissues, which was unexpected given that high SQLE mRNA expression is a risk factor for progression of this cancer [66]. However, the reduction in total SM was accompanied by a marked increase in the proportion of the stable and constitutively active trunSM.…”
Section: Discussionmentioning
confidence: 85%
“…In colorectal cancer, SQLE is upregulated in tumor tissues compared with normal tissues, but SQLE in stages I, II, and III is higher than that in stage IV ( 22 , 23 ). Similarly, SQLE is upregulated in nasopharyngeal cancer ( 13 ), head and neck squamous cell carcinoma ( 24 ), leukemia ( 25 ), hepatocellular cancer ( 26 28 ), and squamous lung cancer ( 29 , 30 ).…”
Section: Sqle Is Highly Expressed In Cancermentioning
confidence: 99%